Innate DNA sensing mechanisms and PYHIN protein function in epithelial cell lines - Massa, Davide (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2016)
In the last decade mechanisms for innate immune sensing of pathogens and self nucleic acids have been defined. For cytosolic sensing of DNA, the adaptor protein STING has a central role, operating downstream of DNA sensors such as cGAS and the PYHIN protein IF116 to mediate transcription factor activation and cytokine and interferon induction. However most of the work in defining cytosolic DNA sensing pathways has been done in monocytic cells, while sensing mechanisms in other frontline sensing cells such as airway epithelial cells have been less well defined. Thus here we analysed the innate immune response of human airway epithelial cell line models to RNA and DNA, in comparison to a human monocytic cell line. Our results show that in both monocytic and transformed epithelial cells the innate immune response to RNA virus and dsRNA was promptly activated. However compared to monocytic cells, A549 and BEAS-2B epithelial cells failed to produce inflammatory cytokines and interferons in response to DNA viruses and dsDNA. These cells lacked expression of IFI16 or STING, but did express cGAS. Ectopic expression of STING restored the DNA response in A549 cells, in a cGAS-dependent manner. In contrast to A549 and BEAS-2B cells, the hTERT-immortalised normal airway epithelial cell line NuLi-1 did express IFI16, cGAS and STING, and responded to DNA stimulation. However, fibroblastic HT1080 cells did not respond to DNA virus infection or DNA ligand transfection despite a protein expression profile similar to the Nuli-1 cell line. These results pointed out a possible intrinsic STING-related signaling pathways suppression mechanism in some transformed cell lines, highlighting the importance in considering different cell models for innate sensing studies in airway epithelial cells.
Keywords: Biochemistry and Immunology, Ph.D.; PhD Trinity College Dublin, 2016